Biomedical Application of Dental Tissue-Derived Induced Pluripotent Stem Cells - Jung-Hwan Lee; Seog-Jin Seo (Stem Cells International)
The academic researches and clinical applications in recent years found interest in induced pluripotent stem cells (iPSCs-) based regenerative medicine due to their pluripotency able to differentiate into any cell types in the body without using embryo. However, it is limited in generating iPSCs from adult somatic cells and use of these cells due to the low stem cell potency and donor site morbidity. In biomedical applications, particularly, dental tissue-derived iPSCs have been getting attention as a type of alternative sources for regenerating damaged tissues due to high potential of stem cell characteristics, easy accessibility and attainment, and their ectomesenchymal origin, which allow them to have potential for nerve, vessel, and dental tissue regeneration. This paper will cover the overview of dental tissue-derived iPSCs and their application with their advantages and drawbacks.